PENGELOLAAN PEMUNGUTAN PAJAK OLEH BADAN PENDAPATAN DAERAH (BAPENDA) KOTA PEKANBARU - Dewi Safutri; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Local Tax is an asset of Regional Government which is used to finance the implementation of Regional Government and regional development. One source of Regional income is derived from local tax levies, taxes levied by the region based on tax regulations set by the region for the benefit of household financing as material public law. The research aims to know Tax Collection Management and Factors that obstacle the management of tax collection.The concept of theory used in this research is Management according to PradjudiAtmosudirdjo which explains about the management function, which consists of 5 indicators namely, planning, organizing, direction, coordination, and controlling. This study aims to find out about the Management of Local Tax Collection ByInstitution of Regional Income(BAPENDA) Pekanbaru City. This research uses qualitative descriptive research method. In collecting this data collection using techniques, interviews, observation, and documentation. Using the Snowball Sampling technique as a source of information.The results showed that the management of local tax collection is still very low and has not reached the expected realization due to lack of awareness and honesty of the community in paying taxes, still less supervision by officers and efforts to manage data that has not been maximized. This research suggests that the Institution of Regional Incomebefore determining the target calculation, it is necessary to conduct field data collection on the potential of each tax, so that the potential of each tax can be realized well and can reach the acceptable income area. Factors that obstacle Tax Collection Management among others: Lack of Human Resources (HR), lack of facilities and infrastructure, lack of awareness and public honesty (taxpayers).Keywords: Planning, Implementation, Controlling, Tax Collection